Broad Spectrum project: factors determining the quality of antibiotic use in primary care: an observational study protocol from Italy. Issue 7 (6th July 2020) - Kurotschka, Peter Konstantin; Serafini, Alice; Massari, Marco; Da Cas, Roberto; Figueiras, Adolfo; Forte, Viviana; Moro, Maria Francesca; Massidda, Matteo; Contu, Federico; Minerba, Luigi; Marcias, Maurizio; Nardelli, Marco; et al.
Abstract : Introduction: The overuse of antibiotics is causing worldwide spread of antimicrobial resistance (AMR). Compared with other countries, Italy has both high antibiotic consumption rates and high rates of AMR. Due to the fact that around 90% of antibiotics are prescribed by general practitioners (GPs), this study aims to measure the impact of knowledge, attitudes and sociodemographic and workplace-related factors on the quality of antibiotic prescriptions filled by GPs in the Italian Region of Sardinia. Methods and analysis: Knowledge, attitude, sociodemographic and workplace-related factors deemed to influence physicians prescribing behaviour will be evaluated in a cross-sectional study conducted among all GPs of the Italian Region of Sardinia (n=1200). A knowledge and attitudes questionnaire (Knowledge and Attitudes on Antibiotics and Resistance - Italian version: ITA-KAAR) accompanied by a sociodemographic form will be linked to drug prescription data reimbursed by the National Health System. European Surveillance of Antibiotic Consumption quality indicators for outpatient antibiotic use will be calculated from drug prescription records. Every GP will be deemed to have demonstrated an adequate quality of prescriptions of antibiotics if half of the indicator score plus one is better than the median of the region. A multivariate Poisson regression model with robust variance estimation will be used to evaluate the impact of the determinants of antibiotic prescriptions on the actual prescribing quality of each physician. Ethics and dissemination: The project has been approved by the ethics committee of the Regional Health Trust of Sardinia (176/2019/CE, 24 September 2019). The results will be useful to inform evidence-based interventions to tackle irrational antibiotic use in the community.